Five new species of Ceratoppia (Acari: Oribatida: Peloppiidae) from western North America - Lindo, Zoe (Zootaxa, 2011)
I present the systematics and distribution of five new species of oribatid mites in the genus Ceratoppia (Oribatida: Peloppiidae) from western North America. The species are described on the basis of adult morphology using the following character states: number of hypostomal setae, number, length and expression of posterior notogastral setae, length of lamellae and lamellar cusp, length of interlamellar setae, and the shape and dentition of the rostrum. Ceratoppia indentata n. sp. is described from forest floor habitats, while Ceratoppia longicuspis n. sp. and Ceratoppia tofinoensis n. sp. are described from arboreal bryosphere habitats; Ceratoppia offarostrata n. sp. is associated with bark habitats. Ceratoppia valerieae n. sp. was collected from both arboreal and forest floor samples. Distributions of all species are provided based on museum and collection records; C. indentata, C. longicuspis, C. tofinoensis are recorded from coastal temperate coniferous rainforests of the Pacific Northwest of North America, while C. valerieae was found in coastal temperate rainforests and extending along the southern border of British Columbia into eastern Alberta. Ceratoppia offarostrata is collected only from a small number of locations on the west coast of Canada. Comments on other North American Ceratoppia species is given. A morphological key is presented to the described adult species for the genus Ceratoppia in North America.